Mortality in minor patients with diagnosis of dengue and its relationship with the use of Dipirone - Gutierrez Lesmes, Oscar Alexander; Plata Casas, Laura Inés; Montaño Contreras, Sandra Carolina (Universidad y Salud, 2016)
Introduction: Dengue is one of the ten most frequent causes of hospitalization in the emergency department of pediatrics where Dipyrone is used as an antipyretic in the symptomatic care. The clinical management guide for dengue of the Panamerican Health Organization (PHO) evidences restrictions for its use in patients with dengue, and according to the Integral Clinical Care Guide for patients with dengue, it should not be administered in pediatric patients. Objective: To determine the relationship between the uses of Dipyrone with the cases of mortality in children under 16 who suffered from dengue in Meta. Materials and methods: A case-control study was conducted based on mortality from dengue in minors reported to the Surveillance System in Public Health in the department of Meta, from 2008 to 2011. Results: The odds ratio (OR) shows that dengue mortality is 17.6 times greater in children Dipyrone treated with a confidence interval of 95% between 3.7 to 84.5 and a P value of 0.0002. Conclusion: The case group who received Dipyrone in their treatment had a higher mortality. There is no evidence or results in the literature review about the relationship of Dipyrone and mortality in children with dengue. This phenomenon should continue to be studied to have greater scientific evidence.